ANALISIS MOTIF PENGGUNAAN SKINCARE PADA SANTRI PUTRI MADRASAH ALIYAH PONDOK PESANTREN AL-AMIN MOJOKERTO - Laurent Nemta Zula Latmafanie; Sri Dwiyanti; Nieke Andina Wijaya; Octaverina Kecvara Pritasari (Program Studi Pendidikan Tata Rias, 2026)
The increasing trend of skincare use among teenagers is also evident in Islamic boarding schools (pesantren), despite the prevailing perception that such institutions have limited access to personal care. This study aims to analyze the motives behind skincare use among female students (santri putri) of Madrasah Aliyah at Pondok Pesantren Al-Amin Mojokerto. The research employs a qualitative approach using a phenomenological method. Data were collected through in-depth interviews, observations, and documentation, and then analyzed using data reduction, data display, and conclusion drawing techniques. The validity of the data was tested through source triangulation. The subjects of this study were female students who actively used skincare products within the pesantren environment. The findings revealed three main motives for skincare use among the students: social motives (peer influence, social media trends, and institutional support for personal care), psychological motives (the desire to boost self-confidence, personal comfort, and practicing self-care), and biological motives (the need to maintain skin health from issues such as acne, dullness, and environmental factors). The findings suggest that skincare has become a way for santri to adapt in addressing their personal care needs within the context of modern Islamic boarding schools.